Perceptions of Dutch nurses carrying methicillin-resistant Staphylococcus aureus: a qualitative study - Lotte van Heuvel; Renske Eilers; Sabiena G. Feenstra; Manon R. Haverkate; Aura Timen (BMC, 2020)
Abstract Background Carriers of methicillin-resistant Staphylococcus aureus (MRSA) experience a variety of personal and social consequences, despite the asymptomatic nature of carriage. Some of these consequences are inherent to the application in practice of strict infection prevention guidelines. However, the experiences of nurses carrying MRSA have not been documented. This study aimed to describe the experiences of nurses carrying MRSA to get insight into the impact of MRSA carriage on nurses in a country with a "search-and-destroy" policy for MRSA. Methods A qualitative study was conducted among eighteen nurses who experienced MRSA carriage and were working in healthcare organizations in the Netherlands (e.g. hospitals, nursing homes and home care). Semi-structured interviews were conducted using an interview guide. The interviews were audio tape recorded, transcribed and analyzed using thematic analysis. Results MRSA carriage has an impact on the life of nurses during four distinct phases: becoming aware of carrying MRSA, processing information and guidance, experiencing consequences of carriage and, when applicable, a life after eradication of MRSA. Each phase was found to be associated with negative consequences. The impact of MRSA carriage on the daily life of nurses is mostly influenced by the experience of consequences of MRSA carriage - including a ban to work with patients, eradication treatment with antibiotics, and social isolation from others - despite the asymptomatic nature of MRSA carriage itself. In addition, lack of information and guidance increased the impact of carriage. Conclusions This study shows nurses experience various consequences of MRSA carriage, despite the asymptomatic nature of carriage. The work ban, eradication treatment and social isolation influenced the nurses' work-related future, personal health and social environment. The impact of carriage may be reduced by clear information and guidance, and support from others. Therefore, sufficient information and guidance needs to be given to MRSA carriers by healthcare organizations.